The Critical Role of X Chromosome-Linked Inhibitor of Apoptosis (XIAP) in Differential Synergism Induced by Pentachlorophenol and Copper-1, 10-Phenanthroline Complex in Normal and Cancer Liver Cells. (27th December 2018) - Sheng, Zhi-Guo; Shen, Chen; Fan, Rui-Mei; Chao, Xi-Juan; Liu, Yu-Xiang; Zhu, Ben-Zhan
Abstract: Chemical pollutants often co-occur and can interact to cause unexpected combined toxic effects. Both pentachlorophenol (PCP) and copper-1, 10-phenanthroline [Cu(OP)2 ], used as wood preservatives, coexist in fluids and tissues of ordinary population. Our previous studies demonstrate that a combination of subtoxic PCP and Cu(OP)2 causes synergistic toxicity on Escherichia coli and hepatocarcinoma cells. However, it is not clear whether this effect also occurs in normal hepatocytes; and if so, what are the differences as compared with the hepatocarcinoma cells. We demonstrate that the combination of low-toxic PCP and Cu(OP)2 (0–1.6 µM; PCP/Cu(OP)2 molar ratio: 2:1) induces a concentration-dependent intracellular copper accumulation, apoptosis, caspase-3/9 activation, depolarization of mitochondrial membrane potential, and oxidative stress (reactive oxygen species increasing and glutathione/oxidized glutathione ratio decreasing) in both normal hepatocytes HL-7702 and hepatocarcinoma HepG2 cells. However, HepG2 cells are more susceptible to the above molecular events as compared with HL-7702 cells. Further data reveal that PCP/Cu(OP)2 markedly decreases X chromosome-linked inhibitor of apoptosis (XIAP), p -ERK-1/2, and p -JNK protein expression in HepG2, but not HL-7702. Overexpression of XIAP gene in HepG2 significantly blocks PCP/Cu(OP)2 -induced cytotoxicity, caspase activity, apoptosis, ROS accumulation, and antioxidant genes expression. These results suggest that the combination of low-toxic PCP and Cu(OP)2 preferentially induce synergistic cytotoxicity in human hepatocarcinoma cells by XIAP-ROS-apoptosis pathway, compared with the normal hepatocytes. The present data not only confirm the synergistic toxicity of PCP/Cu(OP)2 combination in normal liver cells, but also suggest a possible opportunity in developing new therapeutic approaches for liver cancer by sensitizing cancer cells to chemotherapy.